Applying instructional design in the production of didactic material for the Alfa-Miforcal Project A integrated propose to production material between Unisul Virtual e UniVirtual - Lumi Matuzawa, Flavia (Formazione & insegnamento, 2015)
The article deals with the practice of instructional design in the production of materials for distance learning courses. It first shows the theoretical concepts involved in instructional design process and talk about some care that is necessary, such as: treatment of form, appropriateness of language, use of image, integration of different professionals (subject matter experts, instructional designer, graphic designer, programmer, specialist in audio and video). In particular, the article reports the experience of developing materials and how was to adapt the contents from others universities to the Unisul Virtual’s methodology. Finally, the article aims to awaken some reflections about the materials provided and the role of instructional design about the possible ways of presenting content: print, online and new digital formats (mobility).